The degradation of mechanical properties in polymer nano-composites exposed to liquid media – a review. Issue 2 (22nd December 2015) - Saharudin, Mohd Shahneel; Atif, Rasheed; Shyha, Islam; Inam, Fawad
Abstract : The advancement of polymer nano-composites has been motivated by the need for materials with a specific combination of mechanical properties beyond those achieved from only one material. Abstract : The advancement of polymer nano-composites has been motivated by the need for materials with a specific combination of mechanical properties beyond those achieved from only one material. Integration of reinforcement into polymers at the nanoscale can provide a significant increase in numerous physical and mechanical properties of polymer nano-composites. However, in applications where contact with liquid media is unavoidable, the mechanical properties of polymer nano-composites suffer degradation which is a commonly observed phenomenon. Non aggressive liquid such as water is capable of lowering the mechanical properties of polymer nano-composites by acting as plasticizers while moderate and severe aggressive liquid when combined with residual stresses can cause unexpected brittle failure known as ESC. To date, only a few studies are reported discussing the ability of nano-fillers to resist degradation of mechanical properties in polymer nano-composites when exposed to liquid media. In this review, various factors responsible for mechanical property degradation caused by liquid media in polymer nano-composites and their remedies are studied.